Distribution and Growth Patterns of Crab (P. pelagicus) Based on Environmental Characteristics in Candi Waters, Pamekasan Regency, East Java Province - Leni Maryani; Dietriech Geoffrey Bengen; I Wayan Nurjaya (Jurnal Kelautan Tropis, 2023)
Blue swimming crab (BSC) is a fishery commodity with high economic value and great demand in domestic and foreign markets. P. pelagicus swimming crabs are commonly found in Indonesian sea waters, one of the largest contributors to the country's foreign exchange after shrimp and tuna. The high demand for blue crab resources will trigger an increase in fishing efforts. If this is done continuously, it is feared that it could endanger the population structure. Moreover, disrupting the sustainability of blue swimming crab resources in the waters, this study examines the morphometric distribution and growth pattern of P. pelagicus crabs based on environmental characteristics in Candi waters, Pamekasaan Regency. Census sampling was carried out using the census method; the census method was carried out by taking all crab samples caught by fishermen. The results obtained found 33 individual crabs, which were divided into three classes, namely small (<10 cm), medium (>10 cm), and large (>12 cm) size classes. Male crabs dominated the research locations with wider straps than female crabs. The analysis results show that the width-weight relationship's b values are 1.47 (males) and 2.00 (females). In addition, male and female crabs have a positive allometric growth pattern. Blue swimming crabs are often found in habitats with a substrate of dusty mud, high salinity and organic matter.